Phenolic content and antioxidant activity of Croatian and German honey - Bok Valerija Vujčić; Šola Ivana; Rusak Gordana; Budisavljević Alan; Nguyen Rosa; Ludwig-Müller Jutta; Maleš Željan (Acta Pharmaceutica)
Since honey has a therapeutic role in the treatment of many diseases, we investigated the content of phenolic compounds and the antioxidant activity in acacia (Robinia pseudoacacia L.), chestnut (Castanea sativa Mill.) and lime-tree (Tilia spp.) honey originating from Croatia and Germany. Total phenols, flavonols, and flavanols contents were observed at higher levels in Croatian Castanea honey compared to German Castanea honey. Significant higher values of total flavanols and hydroxycinnamic acids were measured in Croatian Tilia honey compared to German Tilia honey. For Robinia honey, significantly higher values of total phenols and flavonols were observed in almost all Croatian honey samples compared to German honey. Croatian honey samples had higher antioxidant activity compared to German honey samples with most tested methods. The highest total phenols, total flavanols, ABTS, DPPH, and FRAP values were measured in Castanea honey, then in Robinia honey, and the lowest values in Tilia honey samples. With new developed HPLC method, pinobanksin, pinocembrin, and chrysin were identified in the majority of honey samples. Our results imply that both botanical and geographical origin influence the final quality of phenolic compounds and antioxidant activity in honey. A high positive correlation between the results of antioxidant activity and polyphenols was detected.